The Realm of Facts Aspects of Philosophical Realism - Rescher, Nicholas (Epistemic Studies ;, 2020)
Knowledge of facts is essential for the management of life. Most studies of the subject examine how we go about trying to obtain it; they describe the processes and proceedings of rational inquiry. The present work steps back from this to inquire into the limits and limitations of such processes and to identify the assets and the limitabilities of what they are able to supply for us. It examines how knowledge of facts is secured and consolidated as such, and what the resulting information can and cannot provide. It argues that the unavoidable incompleteness of our factual information also endows it with an element of incorrectness. By looking also at the negative side of human inquiry the book's perspective clarifies the nature of our grip on the facts that constitute our view of the reality of things.